Myc functions downstream of InR and their concurrent upregulation additively restricts pathogenesis of human poly(Q) disorders in Drosophila disease models. - Tandon, S.; Sarkar, S. (International Journal of Biochemistry & Cell Biology, 2024)
Human polyglutamine [poly(Q)] disorders are caused by abnormal expansion of CAG repeats in one gene (disease specific), yet a plethora of cellular pathways are found to be involved in their pathogenesis and progression. Despite the tremendous effort, all pursuits for the development of intervention therapy against these disorders seem futile. Recent reports suggest combination therapy as a potential strategy to combat the complex pathogenesis of such neurodegenerative disorders. The present study attempted to identify a combinatorial intervention strategy against human poly(Q) disorders in Drosophila disease models. Due to its immense potential to be stimulated by drugs, the evolutionarily conserved insulin signalling cascade which is well-established modifier of human poly(Q) pathogenesis was selected for the study. Genetic screening studies identified Drosophila Myc as a potential partner of insulin receptor (InR) that conferred additive rescue against poly(Q) induced neurodegeneration. Comprehensive analyses demonstrated InR and Myc to confer additive rescue against several events of pathogenesis, including aggregation of expanded poly(Q) containing proteins, transcriptional dysregulation, upsurge of cell death cascades, etc. Also, the synergistic rescue efficiency of InR and Myc was equally efficient in mitigating poly(Q) induced structural and functional deficits. The study also demonstrates that Myc functions downstream of InR signalling cascade to deliver rescue against human poly(Q) mediated toxicity in Drosophila disease models. In conclusion, the present study suggests that InR and Myc have the potential to be developed as a combinatorial therapeutic approach against human poly(Q) diseases.